Expansion into India and Developing A Business Strategy - Narayanan, Sridhar (2006)
Globalisation is the new buzzword that has come to dominate the world. Several reasons can be attributed to these changes. One of the reasons is globalization, the explosive growth of global trade, International competition and the other is technological change. Market success goes to those companies best matched to the current environmental imperatives. This process is having significant impacts on India and China, two highly populated countries in the world; exemplify the striking similarities and vast differences that characterize the Asian region. Once considered difficult markets to enter,